Beispiel Nr: 01
$ \text{Gegeben:} \\ \text{Ebene in Koordinatenform: } n_1 x_1+n_2 x_2+n_3 x_3+k1=0 \\ \text{Gesucht:} \\ \text{Hessesche Normalenform} \\ k1<0 \\ \text{HNF:} \dfrac{n_1 x_1+n_2 x_2+n_3 x_3+k_1}{\sqrt{n_1^2+n_2^2+n_3^2}}=0 \\ k1>0 \\ \text{HNF:} \dfrac{n_1 x_1+n_2 x_2+n_3 x_3+k_1}{-\sqrt{n_1^2+n_2^2+n_3^2}}=0 \\ \\ \textbf{Gegeben:} \\ \text{Ebene: } 3 x_1+4 x_2+6 x_3+7=0 \\ \\ \\ \textbf{Rechnung:} \\ \text{Koordinatenform in Hessesche Normalenform HNF} \\ 3 x_1+4 x_2+6 x_3+7=0 \\ \vec{n} = \left( \begin{array}{c} 3 \\ 4 \\ 6 \\ \end{array} \right) \\ \text{Länge des Normalenvektors} \\ \left|\vec{n}\right| =\sqrt{n_1^2+n_2^2+n_3^2} \\ \left|\vec{n}\right| =\sqrt{3^2+4^2+6^2} \\ \left|\vec{n}\right| =7,81 \\ \text{HNF:} \dfrac{3 x_1+4 x_2+6 x_3+7}{-7,81}=0 \\ $